Performance analysis of deep bed drying of canola seeds using numerical technique. (December 2021) - Kumar, Dhiraj; Mishra, Ankitendran; Prasad, M.; Pyare, Ram; Majhi, M.R.
Abstract: Canola grain containing 18–20% moisture during harvesting is not suitable for safe storage. The storage conditions for these grains need to be optimized through drying technique to prevent both fungal attack and suppression in germination. Hence, the present investigation has been carried out to analyze coupled heat and mass transfer phenomena during steady state counter flow deep bed drying. To carry out this study, a non-equilibrium drying model has been developed. Governing equations include moisture mass balance, enthalpy balance, heat transfer rate, mass transfer rate for an element along bed height. And diffusion equation of moisture inside a single kernel has also been solved simultaneously through an implicit scheme using TDMA (Tri-Diagonal Matrix Algorithm). An iterative approach has been used to solve the governing equations for a selected geometry of the dryer. The rating analysis can be used for arriving at improved quality and higher efficiency at reasonable level of throughput. Highlights: Coupled heat & mass transfer during drying is analyzed with sequential numerical technique. Continuous flow of rice has been studied for different parameters in deep bed dryer. Non-equilibrium model, rather than thin layer drying, is used. More accurate, detailed and valid results are obtained.